Effect of Compound Planting Mode on Nutrient Distribution in Cotton - Lirong He; Lei Shi; Qiaoni Gao; Guobin Liu; Chutao Liang (Plants)
Composite planting has become one of the primary agricultural practices promoted in recent years, especially in the northwest inland cotton regions of China, where various economic trees and crops are intercropped with cotton. However, research on the microclimatic differences affecting cotton growth and the nutrient allocation strategies for cotton’s key economic organs (i.e., seed, batt, and shell) in strip composite cropping systems remains limited. In this study, we examined the nutrient allocation strategies of cotton under multiple composite cropping patterns and proposed the most suitable cultivation patterns for this region in the northwest inland region of China, utilizing an allometry partitioning index and ecological stoichiometry, based on a long-term positional experiment. The results revealed that the nutrient distribution of cotton was of equal speed with the combined planting with trees, while there was an allometric distribution index of N and P between the combined planting with maize. The effect of the compound planting mode on the nutrient-use efficiency of cotton was mainly reflected in the organ differentiation stage of its reproductive growth stage. Specifically, cotton showed lower nutrient-use efficiency in reproductive organs when intercropped with low shrubs and herbaceous crops, likely due to the insufficient protective capacity of these plants for cotton. Interestingly, strip intercropping with tall trees improved cotton’s nutrient-utilization efficiency. However, it also resulted in reduced nitrogen and phosphorus content in cotton batt. Moreover, soil indicators such as available nitrogen and electrical conductivity positively influenced the nutrient uptake of cotton shells and roots, while soil phosphorus promoted the nutrient absorption of cotton seed but inhibited the nitrogen and phosphorus of cotton shell and the nitrogen of cotton batt. These findings suggest that nutrient partitioning in cotton is influenced by a variety of soil factors. According to these results, the combined planting pattern of cotton and apple trees should be considered in practice to improve cotton yield and economic benefits in the northwest inland region of China.